2012
DOI: 10.1177/0960327112455068
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and antioxidant activity of thymoquinone in a rat model of acute bacterial prostatitis

Abstract: Prostatitis plays a major role in morbidity and mortality related to prostate diseases. The aim of this study was to detect whether thymoquinone (TQ) could ameliorate oxidative damage and the proliferative response induced by Escherichia coli (E. coli) in rats. A total of 42 adult male Wistar rats were used. The rats were randomly divided into seven groups (three treatment groups, three infected groups and one control group). Control group received saline and was killed 24 h after saline administration. Infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…In different toxicity studies it was found that the administration of TQ led to decreased MDA levels [30,33,34,35]. In the present study, TQ protected prostate tissue from NO- and MDA-dependent oxidative stress when administered at 24, 48, and 72 h (p < 0.05; fig.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…In different toxicity studies it was found that the administration of TQ led to decreased MDA levels [30,33,34,35]. In the present study, TQ protected prostate tissue from NO- and MDA-dependent oxidative stress when administered at 24, 48, and 72 h (p < 0.05; fig.…”
Section: Discussionsupporting
confidence: 58%
“…Several clinical and experimental prostatitis studies showed increased MDA levels [25,26,27,28,29,30]. Nelson et al [11] showed that the acute stage of Pseudomonas prostatitis infection was markedly determined on the second day.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…sativa L. seed extract and its active ingredient, thymoquinone, have been characterised as antioxidant and anti-inflammatory agents in different experimental settings (Salem 2005;Inci et al 2013). In light of these considerations, effect of N. sativa L. seed extract on Downloaded by [University of Sussex Library] at 18:37 27 June 2016 cisplatin-induced delay in gastric emptying was investigated in rats.…”
Section: Resultsmentioning
confidence: 99%
“…[10,11,26,28] The use of TQ has shown to have anti-inflammatory effects in several inflammatory diseases, including experimental allergic encephalomyelitis, [29] colitis, [30] arthritis, [31] and bacterial prostatitis. [32] One limitation of this study was the lack of measurement of antioxidant enzyme activities and the degree of membrane lipid peroxidation in the injured spinal cord tissue. The other limitation of this study was the lack of motor testing of the animals.…”
Section: Discussionmentioning
confidence: 98%